Lesbian and bisexual women's health beliefs about performing the Papanicolaou's test - Nathanael de Souza Maciel; Anna Beatriz Justino do Nascimento; Gabriely Bezerra de Castro; Breno Sousa Bandeira; José Gerfeson Alves; Leilane Barbosa de Sousa (Universidade Federal do Ceará, 2023)
Objective: to identify the health beliefs of lesbian and bisexual women about performing the Papanicolaou's test. Methods: cross-sectional study developed exclusively online, with fifty-five participants. Google Forms® were used for data collection, with sociodemographic and economic questions, as well as questions related to practices, intention, and beliefs about performing the Papanicolaou's test. Data were organized in Google Sheets® and analyzed in SPSS® software. Results: it was found that bisexual women believe more in the benefit "when I do the preventive exam, I am relieved" (p=0.047). However, they have higher scores of ashamed for doing the preventive exam (p=0.005). Significant association was identified between having done the exam and perceived benefits (p=0.040); perceived severity and education level (p=0.006); having done the exam (p=0.039); and having fixed partnership (p=0.028). Conclusion: bisexual women believe that performing the exam generates relief, but feelings of shame may hinder adherence to the exam. Lesbian and bisexual women without access to higher education, who never had the exam, and who have multiple sexual partnerships are more vulnerable to cervical cancer. Contributions to practice: reflect on this scenario so that educational strategies are effective for cervical cancer prevention.